Strach z pádu u seniorů ve zdravotnických a sociálních zařízeních - Růžičková, Veronika; Zeleníková, Renáta (Ošetrovateľstvo, 2017)
Aim: The aim of the study was to find out fear of falling in elderly in health care facilities and social care facilities and compare differences in fear of falling according gender and history of falling. Methods: This is a cross-sectional study. Fear of falling was measured by Czech version of standardized questionnaire Fall Efficacy Scale – International (FES-I). Sample was consisted of 162 elderly in age over 65: 76 patients were hospitalized in hospital and 85 patients were in social care facilities. Chi-square test was used to compare fear of falling according gender and history of falling. Results: According the total FES-I score high fear of falling had 51 % elderly from social care facilities and 15 % of elderly hospitalized in health care facilities. The elderly were concerned about falling the most when doing the following activity: walking on an uneven surface, rocky ground (58 %), walking on a slippery surface (55 %), going up or down stairs (51 %). Fear of falling was statisticaly significant higher in elderly lived in social care facilities than in elderly hospitalized in health care facility. Fear of falling was higher in women (p = 0.011) and in elderly who experienced fall (p = 0.002). Conclusion: Fear of falling was higher in women and in elderly who experienced fall. Higher fear of falling was found in elderly in elderly lived in social care facilities than in hospitalized elderly.
Keywords: průřezové studie; Accidental Falls; senioři nad 80 let; Aged; Fear; Health Facilities; domovy pro seniory; Aged, 80 and over; Homes for the Aged; Humans; lidé; zdravotnická zařízení; úrazy pádem; Cross-Sectional Studies; strach; senioři